2014
DOI: 10.4236/ajps.2014.511178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time, Cultivar and Rootstock on Success of Rose Propagation through Stenting Technique

Abstract: An experiment was undertaken to study the effects of two grafting times (1st of June and end of September) as well as kind of rootstock on growth and rooting of rose stentlings. Two Rosa species i.e. R. canina and R. manetti were selected as rootstock and three different hybrid tea rose cultivars namely Avalanch, Peach Avalanch and Dolcevita were grafted on them as scion through omega and splice techniques. The growth parameters were collected 57 days after grafting. The highest average of rooting, healing per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
2
1
0
1
Order By: Relevance
“…In the present study, shoot new growth, number of new shoots, and shoot FW and DW were positively correlated with the root number (R 2 values of 0.70, 0.76, 0.72 and 0.64, respectively, data not shown). This is in line with the finding that in IBA-treated Hibiscus rosa-sinensis rootstock, propagated using stenting, there was a positive correlation between shoot and root number [51]. This may be caused by a higher cytokinin generation in cuttings with a higher root number.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, shoot new growth, number of new shoots, and shoot FW and DW were positively correlated with the root number (R 2 values of 0.70, 0.76, 0.72 and 0.64, respectively, data not shown). This is in line with the finding that in IBA-treated Hibiscus rosa-sinensis rootstock, propagated using stenting, there was a positive correlation between shoot and root number [51]. This may be caused by a higher cytokinin generation in cuttings with a higher root number.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, it was hypothesized that early and delayed incompatibility might be involved with different genes. These findings are in close similarity with the findings of [25], who reported that compatibility is dependent on the presence of a particular factor or absence of the factors in both rootstock and scion in rose. Means followed by similar letters are statistically non-significant / similar at 5 % level of significance.…”
Section: Survival Percentage (%)supporting
confidence: 91%
“…Penggunaan cabang dengan umur yang semakin tua maka akan menurunkan tingkat keberhasilan pencangkokan. Penggunaan cabang yang berdiameter tidak terlalu besar maka semakin besar persentase hidup, hal ini di karenakan karbohidrat dan zat makanan yang masih banyak (Izadi et al, 2014), Tingkat keberhasilan di pengaruhi oleh media tanah dan media pembungkus yang mampu menjaga kelembaban tanah dan juga cabang yang sehat kuat tidak terlalu tua dan tidak terlalu muda dan juga cabang yang lurus ke atas. Hal ini di kuatkan oleh pendapat (Fatikhasari et al, 2021).…”
Section: Persentase Keberhasilanunclassified